Pengaruh Debt Default, Financial Distress dan Ukuran Perusahaan terhadap Penerimaan Opini Audit Modifikasi Going Concern - Reza Purnama Eka Putri; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to test empirically the effect of debt default, financial distress and company size on the acceptance of going concern modification audit opinion. This research uses a quantitative approach with the type of causal research. The population used in this study are mining companies listed on the Indonesia Stock Exchange in 2014-2018. By using purposive sampling method obtained 95 samples. Default debt is measured by dummy variables. Financial Distress is measured by the Grover Model (2001). Company size is measured using LogNatural's total assets. And going concern modification audit opinion is measured using dummy variables. The results show that debt default and financial distress have a significant effect on going concern modification audit opinion acceptance, while company size has a significant negative effect on going concern modification audit opinion. Further research is expected to expand the object and year of research because this study only examines mining companies for the 2014-2018 observation year. For other research, it is expected to add independent variables so that the results are better.